Pedagogical Conditions for The Formation of Professional Culture of Future Educators of Preschool Educational Institutions - Bogush, Alla (2020)
The article reveals the essence of the phenomenon “professional culture of future educators of preschool educational institutions” viewed as a complex integral formation within a holistic structure of a personality. It is characterized by a positive attitude to the subjects and objects of pedagogical activity (axiological component), deep and systematized professional knowledge, skills and competencies (cognitive component), as well as personal and professional qualities that reflect the level of mastery of a special area of knowledge (personal component) and find their manifestation in pedagogical activity (reflexive component). Criteria (specified by indicators) that characterize levels of professional culture development of future preschool educators have been determined, including: informational, motivational, behavioral and appraisal-creative. Pedagogical conditions for the formation of professional culture of future preschool educators in the process of their professional training have been substantiated. The above-mentioned pedagogical conditions presuppose: activation of educational activities of future preschool educators in the cultural and educational environment of a higher pedagogical institution; provision of interactive technological support for the educational process of future preschool educators; integration of the content of normative professional disciplines. The technique of forming the professional culture of future educators of preschool educational institutions is presented.